2018
DOI: 10.4274/tjps.03274
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Polyphenol Composition, Biological Activities and Detoxification Properties of Some Medicinal Mushrooms from Turkey

Abstract: Objectives: Ethanolic extracts of Ganoderma adsperum, Inonotus hispidus, Russula chloroides and Sarcodon imbricatus mushroom species were investigated for their polyphenolic contents and biological activities. Materials and Methods: The radical scavenging activity of the extracts were evaluated by using DPPH 2,2-Diphenyl-1-(2,4,6-trinitrophenyl) method and their polyphenolic compounds were determined by HPLC analysis. Furthermore, the activity effects of mushroom extracts on the GST (glutathione-S-transferase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It is also reported in the literature that the total phenolic and flavonoid content of S. imbricatus is 1.50-13.20 and 1.46-5.45 mg/g, respectively (Barros et al, 2007a,b;Shomali et al, 2019) and contains gallic acid (0.75 mg/g) and myrcetin (2.89 mg/g) (Shomali et al, 2019). It is seen that the total phenolic/flavonoid compound data obtained from the present study differ from the literature data.…”
Section: Discussion and Conclusion 41 Chemical Compositions Of Mushroom Extractsmentioning
confidence: 88%
See 1 more Smart Citation
“…It is also reported in the literature that the total phenolic and flavonoid content of S. imbricatus is 1.50-13.20 and 1.46-5.45 mg/g, respectively (Barros et al, 2007a,b;Shomali et al, 2019) and contains gallic acid (0.75 mg/g) and myrcetin (2.89 mg/g) (Shomali et al, 2019). It is seen that the total phenolic/flavonoid compound data obtained from the present study differ from the literature data.…”
Section: Discussion and Conclusion 41 Chemical Compositions Of Mushroom Extractsmentioning
confidence: 88%
“…In a study conducted by Barros et al (2017c), it was reported that cooking and processing processes reduced the effectiveness of S. imbricatus in the -carotene bleaching test. In other studies on the DPPH radical scavenging activity of S. imbricatus, it has been reported that methanol extract exhibited remarkable efficacy (Marcotullio et al, 2008;Luo et al, 2017;Shomali et al, 2019).…”
Section: Chemical Compositions Of Mushroom Extractsmentioning
confidence: 95%
“…However, ethanol extraction was discovered to be the most effective method for extracting phytochemicals and polysaccharides from the biomass of mushrooms and their fruiting bodies. Shomali et al (2019) examined the polyphenolic contents and biological activities of four wild mushrooms and found that the ethanolic extracts of I. hispidus had the highest total phenolic and flavonoid contents when compared to other mushroom species. Our results also showed high b-glucan, total phenolic, flavonoid, saponin, and Recently, research has focused on the many health benefits of dietary fibers with macrofungal origins.…”
Section: A B Cmentioning
confidence: 99%